Anticancer effects of suberoylanilide hydroxamic acid in esophageal squamous cancer cells in vitro and in vivo. Issue 7 (4th September 2013) - Tzao, C.; Jin, J.‐S.; Chen, B.‐H.; Chung, H.‐Y.; Chang, C.‐C.; Hsu, T.‐Y.; Sun, G.‐H.
Summary The effects of suberoylanilide hydroxamic acid (SAHA), a histone deacetylase inhibitor, have not been studied in esophageal squamous cell cancer (ESCC). Cell viability assay; flow cytometry for cell cycle and annexin V apoptosis assays; assays for cell migration, invasion, and adhesion to extracellular matrix (ECM); and immunoblotting and immunofluorescence staining were performed in three ESCC cell lines. Tumor xenograft with semiquantitative immunohistochemistry was used to study the effects of SAHA in vivo. SAHA effectively inhibited growth of ESCC cells with half‐inhibitory concentrations (IC50) ranging from 2.6 to 6.5 μmol/L. SAHA restored acetylation of histone 3 lysine 9 (H3K9Ac) and histone 4 lysine 12 (H4K12Ac) with an induction of G1 or G2 cell cycle arrest and apoptosis. Expression of cell cycle checkpoint regulatory proteins including cyclin‐dependent kinases (CDKs) and cyclins was decreased, whereas expression of cell cycle suppressors, p21, p27, and Rb was increased in ESCC cells after SAHA treatment. SAHA inhibited migration, invasion, and ECM adhesion in ESCC cells with an induction of E‐cadherin expression. SAHA significantly inhibited growth of ESCC tumors with increased expression of p21, p27, Rb, and E‐cadherin while decreasing expression of CDK4 and cyclin D1 within the murine tumors. In conclusion, SAHA had antigrowth activity against ESCC cells in vitro and in vivo while inhibiting cell migration, cell invasion, and ECM adhesion, suggesting its potential as an epigenetic therapeutic agent for ESCC.